Southern African bean improvement nursery - National Bean Programme (National Bean Programme, 1990)
The yield of South African bean lines was assessed in Malawi, using 3 groups with 15 genotypes each. In the 1st trial, carried out in 4 different agroecological zones, Carioca 80 was the best genotype with high yields at all sites (712-1768 kg/ha) and resistant to angular leaf spot and rust. Other genotypes performed well at several sites: BAT 1514, PVBZ 1782, PVA 340, PVA 773, PVA 262, PVBZ 1589, and PVBZ 1713. Highest yields were obtained in Dedza (av. 1523 kg/ha) and the lowest in Matapwata (av. 276 kg/ha). BAT 1514, PVBZ 1589, and PVBZ 1782 were also resistant to angular leaf spot and rust in Champhira and Lunyangwa. All cv. were susceptible to floury leaf spot. In the 2nd trial, also conducted at 4 different sites, the highest yields (av. 889 kg/ha) and the greatest resistance to angular leaf spot (av. 1.7) were obtained in Mzimba. The best South African genotypes were Umvoti, Kompasberg, H 7822-C2, PC 222-5-D2, PC 166-C39, and Enselini. Seed size was generally large in Champhira, with 100-seed wt. of 52 g. All genotypes were susceptible to angular leaf spot and rust, but several were resistant to Ascochyta in Bunda. In the 3rd trial, carried out in Bunda, local genotype Nyauzembe had the highest production (1016 kg/ha), followed by the South African lines PC 213- C3, Umvoti, Type 2 White, PC 167-C6, and PC 351-19 (772, 740, 671, 731, and 647 kg/ha, resp.). Generally all the South African lines had small seeds and high susceptibility to rust. (CIAT)